2012
DOI: 10.1093/geront/gns126
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Stress Reduction for Family Caregivers: A Randomized Controlled Trial

Abstract: MBSR could reduce stress and improve mental health in caregivers of family members with dementia residing in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
198
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(211 citation statements)
references
References 56 publications
7
198
1
5
Order By: Relevance
“…Caregiver interventions tested in these studies can be broadly categorized into two groups. The first group included 3 pilot trials of single component interventions focused on caregiver stress reduction via meditation techniques: yogic meditation (Lavretsky et al, 2013), transcendental meditation (Leach, Francis, & Ziaian, 2014), and mindfulness meditation (Whitebird et al, 2013). Outcomes concerned stress and depression, although one study comparing yogic meditation to relaxing music included biomeasures of telomerase activity in peripheral blood (Lavretsky et al, 2013).…”
Section: Results From New Intervention Studiesmentioning
confidence: 99%
“…Caregiver interventions tested in these studies can be broadly categorized into two groups. The first group included 3 pilot trials of single component interventions focused on caregiver stress reduction via meditation techniques: yogic meditation (Lavretsky et al, 2013), transcendental meditation (Leach, Francis, & Ziaian, 2014), and mindfulness meditation (Whitebird et al, 2013). Outcomes concerned stress and depression, although one study comparing yogic meditation to relaxing music included biomeasures of telomerase activity in peripheral blood (Lavretsky et al, 2013).…”
Section: Results From New Intervention Studiesmentioning
confidence: 99%
“…The fact that only the experimental group included a man, the controls all being women, could also influence the results obtained, and the possible differences between genders in the effectiveness of MBP have not been controlled for in the analysis. Another limitation is the lack of burden measures after the MBP program, even though previous research has found a mindfulness intervention to have little effect on burden (Whitebird et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…MBSR has been shown to improve coping skills, self-reflection, awareness and acceptance. In the context of caregivers for individuals with dementia, MBSR has been shown to decrease depression, lower stress, and improve mental health, anxiety, and burden (Whitebird et al, 2012). …”
Section: Assessing and Intervening: Aggression In Dementiamentioning
confidence: 99%